1, 2‐Aminofunctionalization Reactions of Pyridino‐Alkynes via Carbophilic Activation. Issue 12 (20th October 2021) - Paroi, Bidisha; Sancheti, Shashank P.; Patil, Nitin T.
Abstract: Transition metal‐catalyzed 1, 2‐difunctionalization reactions of alkynes have emerged as a powerful tool to forge carbon–carbon and carbon–heteroatom bonds for the rapid synthesis of polyfunctionalized molecular scaffolds. In this regard, our group has persistently been developing transition metal‐mediated 1, 2‐aminofunctionalization reactions of alkynes through a rationally designed pyridino‐alkyne core by utilizing the carbophilic activation strategy. In this account, we present an array of such 1, 2‐aminofunctionalization reactions which have been successfully executed on this core to afford important polycyclic frameworks such as functionalized quinalizinones, pyridinium oxazole dyads (PODs), N‐doped polycyclic aromatic hydrocarbons (PAHs), N‐doped spiro‐PAHs. Additionally, the synthesis of phosphine ligated gold complexes bearing pyrido‐isoquinoline scaffold from the pyridino‐alkynes will be discussed briefly. Abstract : This personal account comprises the annals of 1, 2‐aminofunctionalization reactions of pyridino‐alkynes utilizing the carbophilic activation property of Cu, Ag and Au. Based on the diversely functionalized handles of these pyridino‐alkynes and applied metal catalysts, various divergent reactivities have been disclosed herein with a particular focus placed upon understanding the mechanistic aspects of the transformations.